A Case Report on Scalp edema in a case of HSP in a young adult - Thapaliya, S.; Nepal, M.; Nepal, B.; Pathak, R. (Journal of Advances in Internal Medicine, 2019)
Henoch Schonlein Purpura (HSP) is a systemic small vessel vasculitis which most commonly affects children. HSP is characterized by non-thrombocytopenic palpable purpura, arthritis or arthalgia, gastrointestinal and renal involvement. Scalp edema is uncommon in children over 3 years. Early recognition, especially outside of the typical age group, with appropriate management can reduce morbidity and organ damage. We present a case of a young adult with HSP who